2021
DOI: 10.1002/pi.6202
|View full text |Cite
|
Sign up to set email alerts
|

Surface modified microfibrillated cellulose‐poly(vinylidene fluoride) composites: β‐phase formation, viscoelastic and dielectric performance

Abstract: The effect of silylation of microfibrillated cellulose (MFC) surfaces on β‐phase formation in poly(vinylidene difluoride) (PVDF) and the resulting viscoelastic and dielectric performance of MFC‐PVDF composites is investigated. Two different organosilanes, namely aminated (A) and fluorinated (F), were used. Composites of PVDF and MFC at concentrations up to 10 wt%, both untreated and silylated, were prepared by solvent casting. The two different surface modifications did not markedly change the melting and crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…In a similar study, Poothanari et al reported a dielectric constant $10 with the addition of 1 wt% microfibrillated cellulose in PVDF matrix. 31 An enhanced dielectric constant of PVDF filled with 15 wt% cellulose nanocrystals of $47 was also reported by Lizundia et al 32 This article reports the synthesis of freestanding, flexible films of cellulose/PVDF. It also investigates the modulation in the morphological, microstructural, vibrational, and dielectric properties of the resulting films.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In a similar study, Poothanari et al reported a dielectric constant $10 with the addition of 1 wt% microfibrillated cellulose in PVDF matrix. 31 An enhanced dielectric constant of PVDF filled with 15 wt% cellulose nanocrystals of $47 was also reported by Lizundia et al 32 This article reports the synthesis of freestanding, flexible films of cellulose/PVDF. It also investigates the modulation in the morphological, microstructural, vibrational, and dielectric properties of the resulting films.…”
Section: Introductionsupporting
confidence: 66%
“…Thus, by suitably adjusting the ratio of the fillers to the host polymer, the composition can be tuned and a semi‐biodegradable freestanding, flexible film can be achieved which can be used for flexible device applications. In a similar study, Poothanari et al reported a dielectric constant ~10 with the addition of 1 wt% microfibrillated cellulose in PVDF matrix 31 . An enhanced dielectric constant of PVDF filled with 15 wt% cellulose nanocrystals of ~47 was also reported by Lizundia et al 32 …”
Section: Introductionmentioning
confidence: 62%
“…Figure 1a shows the FTIR spectra of reference and heat-treated films. In all cases, the characteristic peaks of cellulose structures are systematically visible (O-H stretching between 3600 and 3300 cm −1 , C-H stretching at 2900 cm −1 , C-C stretching around 1640 cm −1 , CH 2 stretching at 1432 cm −1 and 900 cm −1 , C-H bending at 1373 cm −1 , asymmetric vibrations of C-O-C and stretching of C-O at 1100, 1053, and 1028 cm −1 ) [34,35]. The peak intensity at 3325 cm −1 was reduced after heat treatment due to the decrease in the number of free hydroxyl groups, a consequence of the increase of crystalline cellulose [36].…”
Section: Structure and Morphology Analysis Of Mfc-clay Composite Filmsmentioning
confidence: 99%
“…Figure 2 shows the XRD spectra of the clay and the reference and heat-treated films. The silylated films were not investigated as it was shown that this treatment does not change the crystal structure of cellulose in MFC [34]. The clay displays characteristics peaks at 7.5 • ,19.6 • , 28.6 • , and 35.4 • corresponding to the (001), (100), (004), and (110) lattice planes of clay, respectively [41,42].…”
Section: Structure and Morphology Analysis Of Mfc-clay Composite Filmsmentioning
confidence: 99%